Enhance The Awareness Of Food Waste Management Through The Digital World - Maria Advenita Gita Elmada; Angga Ariestya; Citra Indah Lestari; Theresia Lavietha V. Lolita; Rani Aryani Widjono (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2020)
Food waste is one of many environmental issues in Indonesia that need to be solved. One of the solution to the problem is to manage the food waste and turn it to be something useful such as biogas and organic fertilizer. Yayasan Rumah Energi, an Indonesian NGO, is focusing themselves in this matter, they already found the way to manage the food waste, but then, they still need help to spread the awareness to the society. To help the organization, the team then using the digital world, to reach more people in the society. Another reason of using the digital channel is that in the time of pandemic, it is not possible to host an off-air event. The activity starting from analyzing the problem of the communication, setting the goals and objectives, preparing the strategy, coaching the communication personnel, and hosting digital event. Through the digital event, the team has raised awareness and get more people interested in the matter of food waste management